2002
DOI: 10.1055/s-2002-31947
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Reaction of Azulenyl-4,4,5,5-tetramethyl-1,3,2-dioxaborolanes with Haloazulenes

Abstract: In order to study the physicochemical properties of azulene oligomers, the synthesis and a coupling reaction of 2-(2-amino-1,3-bisethoxycarbonyl-6-azulenyl)-4,4,5,5-tetramethyl-1,3,2-dioxaborolane (1) and 2-(2-azulenyl)-4,4,5,5-tetramethyl-1,3,2-dioxaborolane (2) were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 2 publications
1
32
0
Order By: Relevance
“…11 However, in our initial experiments in the cross-coupling reaction with aryl halides, 6 was found to be inefficient under similar conditions to Miyaura-Suzuki's (Table 2). Concretely, the reaction of 6 with 11a in the presence of PdCl 2 (PPh 3 ) 2 catalyst produced the desired 2-(4-tolyl)azulene (12) 21 in mediocre yield (39%) together with undesired 2-phenylazulene (13) 21,22 (entry1) (Chart 1).…”
Section: Miyaura-suzuki Cross-coupling Reactionmentioning
confidence: 68%
See 1 more Smart Citation
“…11 However, in our initial experiments in the cross-coupling reaction with aryl halides, 6 was found to be inefficient under similar conditions to Miyaura-Suzuki's (Table 2). Concretely, the reaction of 6 with 11a in the presence of PdCl 2 (PPh 3 ) 2 catalyst produced the desired 2-(4-tolyl)azulene (12) 21 in mediocre yield (39%) together with undesired 2-phenylazulene (13) 21,22 (entry1) (Chart 1).…”
Section: Miyaura-suzuki Cross-coupling Reactionmentioning
confidence: 68%
“…9,10 The direct boronate formation of 2-iodoazulene (3b) utilizing Pd-catalyst has been revealed to be a convenient method for preparing 2-azulenylboronate (6) (Scheme 1). 11 However, the yield of the boronate 6 remains so far at most 42%. More recently, Ir-catalyzed reaction of azulene (7) with bis(pinacolato)diboron (4) has improved the yield of the desired 2-azulenylboronate (6) to 70%, in spite of the formation of undesirable 1-azulenylboronate (8) in a certain amount (10%) (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…8 Although the various efficient and facile synthetic methods for azulene derivatives have also been developed in recent years, 9 there are few works in the literature for the synthesis and properties of azulene-substituted pyrrole derivatives. In 2002, Murafuji et al reported the preparation of 2,5-di(6-azulenyl)pyrrole derivative by the Suzuki-Miyaura cross-coupling reaction of 6-azulenylboronic acid ester with a 2,5-dibromopyrrole derivative. 10 Eichen and co-workers demonstrated the Stille cross-coupling reaction of 2-(tributylstannyl)pyrrole with 1,3-dibromoazulene to afford 1,3-di(2-pyrrolyl)azulene in moderate yield.…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, we have advanced with the development of an efficient synthetic method for 2-and 6-thienylazulene derivatives that should contribute to the construction of the organic materials. 7,8 Although the borylation of 3 proceeds relatively efficiently with good product yield (73%), the total yield of the desired biaryl-type compounds from 3 became relatively low due to the two-step protocols (i.e., borylation and the following cross-coupling reaction). 5 Although the azulenyl metal reagents were useful for the preparation of polyaromatic systems with multiple 2-and 6-azulenyl groups, preparation of the metal reagents for the transition-metalcatalyzed reactions sometimes causes difficulty and the most promising azulenylborane reagents are relatively unstable and undergo easy hydrolysis to afford hydrocarbon derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…3 Since the 2-and 6-positions of azulene derivatives are usually inert to the electrophilic substitution reactions in contrast to the high reactivity at those of 1-and 3-positions, 4 we have developed several synthetic procedures for 2-and 6-arylazulene derivatives by utilizing transition-metal-catalyzed crosscoupling reactions (e.g., Suzuki-Miyaura and Stille cross-coupling reactions) of 2-and 6-azulenyl metal reagents. 7 We have also reported an efficient synthetic procedure by utilizing aryl-and heteroarylmagnesium ate complexes including 2-and 3-thienyl derivatives, which are generated in situ from the corresponding aryl and heteroaryl halides, to afford 2-and 6-(aryl-and heteroaryl)azulenes in sufficient yield. 6 Murafuji and co-workers also reported the synthesis of biaryltype compounds containing the 2-amino-6-azulenyl moiety by the Suzuki-Miyaura cross-coupling reaction of the corresponding aryl halides with the 6-borylazulene derivative, which is prepared by the Miyaura-Ishiyama borylation reaction of 3 (structure of 3 is shown in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%